A fatal case of hemophagocytic lymphohistiocytosis associated with gestational psittacosis without symptoms of pneumonia. Issue 12 (12th September 2022) - Yoshimura, Michinobu; Shimizu, Kanako; Nakura, Yukiko; Kawahara, Kazumi; Katano, Harutaka; Motooka, Daisuke; Takeuchi, Makoto; Nagamune, Kisaburo; Imamura, Yoshiaki; Nakamura, Shota; Yasukawa, Kiyoshi; Hasegawa, Hideki; et al.
Abstract: Psittacosis is a zoonotic infection caused by Chlamydia psittaci . Most patients present with acute respiratory symptoms and systemic illness. When C. psittaci infects pregnant women, it causes severe clinical manifestations called gestational psittacosis. Here we report a case of gestational psittacosis. Our patient lacked respiratory symptoms, and pathological postmortem examinations revealed severe placentitis. Both DNA and immunohistochemical analyses were positive for C. psittaci from formalin‐fixed paraffin‐embedded tissues. The chlamydial DNA in the placenta was about 100 times more abundant than that in the lungs; therefore, the placenta rather than the lungs was the probable target of the C. psittaci infection during this pregnancy. We could not identify the source of infection. Gestational psittacosis should be considered in the differential diagnosis for fever of unknown origin during pregnancy, even in cases lacking respiratory symptoms.